Evolução do modelo de negócio no processo empreendedor de start-ups: um estudo exploratório - Aquino, Marcos William de (2015)
The business model is a central construction in entrepreneurship research, representing a strategic framework for conceptualizing a value-based enterprise, allowing the user to design, describe, categorize, criticize and analyze a business model of any company. Thus the study of business models in entrepreneurship is highly relevant as it reflects the business idealization in a definable opportunity, establishing important target that drives entrepreneurial action in organizational endowment and the border of implementing organizational activities. From the business model approach through the logic of how to create , set and appropriate from the value, this study aims to describe the evolution of business models over entrepreneurial process of startup companies. This is a descriptive research, performing the qualitative method, based on the process perspective, that is concerned with the understanding of how things, people, organizations, strategies, environments, change, act and evolve over time and by evolving this way, standing the process, basically stories about what has happened and who, what and when it has been done, that is, events, activities and choices ordered over time. The processes discussed here refer to the processes of creation and set and appropriation of the value that make the business models of start-ups.the following Companies have been interviewed: Cultcultura, Dumom, Bluefive and Reuni.me respectively by their representatives: Thais, Rafael, Marcio and Daniel. The main results of this study point to eight phases of the entrepreneurial process: training, diagnosis, monitoring, testing, networking, recognition, loyalty and expansion. Throughout these stages are identified distinct stages of the processes of creation, value setting and ownership in each of the analyzed start-ups.